Thrombus‐targeted perfluorocarbon‐containing liposomal bubbles for enhancement of ultrasonic thrombolysis: in vitro and in vivo study. Issue 8 (14th August 2013) - Hagisawa, K.; Nishioka, T.; Suzuki, R.; Maruyama, K.; Takase, B.; Ishihara, M.; Kurita, A.; Yoshimoto, N.; Nishida, Y.; Iida, K.; Luo, H.; Siegel, R. J.
Summary Background External low‐frequency ultrasound (USD) in combination with microbubbles has been reported to recanalize thrombotically occluded arteries in animal models. Objective The purpose of this study was to examine the enhancing effect of thrombus‐targeted bubble liposomes (BLs) developed for fresh thrombus imaging during ultrasonic thrombolysis. Methods In vitro: after the administration of thrombus‐targeted BLs or non‐targeted BLs, the clot was exposed to low‐frequency (27 kHz) USD for 5 min. In vivo: Rabbit iliofemoral arteries were thrombotically occluded, and an intravenous injection of either targeted BLs (n = 22) or non‐targeted BLs (n = 22) was delivered. External low‐frequency USD (low intensity, 1.4 W cm−2, to 12 arteries, and high intensity, 4.0 W cm−2, to 10 arteries, for both the targeted BL group and the non‐targeted BL group) was applied to the thrombotically occluded arteries for 60 min. In another 10 rabbits, recombinant tissue‐type plasminogen activator (rt‐PA) was intravenously administered. Results In vitro: the weight reduction rate of the clot with targeted BLs was significantly higher than that of the clot with non‐targeted BLs. In vivo: TIMI grade 3 flow was present in a significantly higher number of rabbits with USD and targeted BLs than rabbits with USD and non‐targeted BLs, or with rt‐PA monotherapy. High‐intensity USD exposure with targeted BLs achieved arterial recanalization in 90% of arteries, and the time to reperfusion was shorter than with rt‐PA treatment (targeted BLs, 16.7 ± 5.0 min; rt‐PA, 41.3 ± 14.4 min). Conclusions Thrombus‐targeted BLs developed for USD thrombus imaging enhance ultrasonic disruption of thrombus both in vitro and in vivo.